2007
DOI: 10.1557/jmr.2007.0133
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of rare-earth-doped hafnia

Abstract: The enthalpies of formation of rare-earth (RE)-doped Hf 1−x RE x O 2−x/2 solid solutions (RE ‫ס‬ Sm, Gd, Dy, Yb; x ‫ס‬ 0.25 to 0.62) with respect to the oxide end members, monoclinic HfO 2 and C-type REO 1.5 , were determined using oxide melt solution calorimetry. The enthalpies of formation fit a function quadratic in composition. The strongly negative interaction parameters in all solid solutions confirm a strong tendency for short-range order. Though strongly negative for all systems, the interaction parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 27 publications
3
44
0
1
Order By: Relevance
“…Zr 1− x RE x O 2− x /2 samples with 20–65 mol% REO 1.5 (RE=Sm, Gd, Dy, Yb, Sc) were synthesized by a coprecipitation method 12,13 . 0.3 M solutions of zirconium oxychloride (ZrCl 2 O·8H 2 O, Alfa‐Aesar, 99.9%) and 0.3 M solutions of rare earth and scandium chloride solutions (SmCl 3 · x H 2 O, Alfa‐Aesar, 99.99%; GdCl 3 ·6H 2 O, Alfa‐Aesar, 99.99%; DyCl 3 · x H 2 O, Alfa‐Aesar, 99.99%; YbCl 3 · x H 2 O, Alfa‐Aesar, 99.99%, ScCl 3 ·6H 2 O, Alfa‐Aesar, 99.99%) were mixed in the appropriate ratio to produce the desired composition.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zr 1− x RE x O 2− x /2 samples with 20–65 mol% REO 1.5 (RE=Sm, Gd, Dy, Yb, Sc) were synthesized by a coprecipitation method 12,13 . 0.3 M solutions of zirconium oxychloride (ZrCl 2 O·8H 2 O, Alfa‐Aesar, 99.9%) and 0.3 M solutions of rare earth and scandium chloride solutions (SmCl 3 · x H 2 O, Alfa‐Aesar, 99.99%; GdCl 3 ·6H 2 O, Alfa‐Aesar, 99.99%; DyCl 3 · x H 2 O, Alfa‐Aesar, 99.99%; YbCl 3 · x H 2 O, Alfa‐Aesar, 99.99%, ScCl 3 ·6H 2 O, Alfa‐Aesar, 99.99%) were mixed in the appropriate ratio to produce the desired composition.…”
Section: Methodsmentioning
confidence: 99%
“…Eight to 12 data points were collected for each ZrO 2 –REO 1.5 sample. The calorimetric methodology was applied previously for a study of the energetics of HfO 2 –REO 1.5 solid solutions 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the estimated transition enthalpies are very approximate. In a recent high-temperature solution calorimetry study of the HfO 2 -GdO 1.5 system, Simoncic et al 22 reported that the formation enthalpy from monoclinic HfO 2 and C-type GdO 1.5 showed a strongly curved trend with negative heat of mixing. The quadratic fit of ⌬H DS as a function of the GdO 1.5 concentration gave an interaction parameter (as in a regular solution) of −237 ± 10 kJ/mol and an estimated transition enthalpy of GdO 1.5 from C-type to fluorite phase as 62 ± 3 kJ/mol, which is quite different from the value estimated in this study.…”
Section: B Enthalpy Of Drop Solutionmentioning
confidence: 99%